1979
DOI: 10.1210/endo-104-5-1442
|View full text |Cite
|
Sign up to set email alerts
|

Diethylstilbestrol and Estradiol Binding to Serum Albumin and Pregnancy Plasma of Rat and Human*

Abstract: The equilibrium binding of diethylstilbestrol (DES) and 17 beta-estradiol (E2) to plasma proteins has been characterized. DES exhibits a 10- to 20-fold greater binding affinity index for bovine serum albumin and rat plasma than E2. As expected, E2 gave high values for binding to plasma from pregnant mice or rats, reflecting the presence of alpha-fetoprotein. DES bound to these samples as it did to bovine albumin and rat plasma. These results suggested that DES ineracts weakly with alpha-fetoprotein. This was v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

1981
1981
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(45 citation statements)
references
References 27 publications
1
44
0
Order By: Relevance
“…The initial model used in our laboratory is the Sprague-Dawley rat given injections of 25 μg estradiol benzoate on neonatal days 1, 3 and 5 of life ( Figure 1). It is important to mention that while this is considered "high-dose", the majority of neonatally administered estradiol is bound to α-fetoprotein which circulates at high levels in neonatal rat serum (42). Consequently, neonatal estradiol is 75-fold less potent than an equivalent dose of DES (43) or, put another way, 25 μg estradiol/pup is equivalent to 0.33 μg DES/pup.…”
Section: Rat Model Of Developmental Estrogenizationmentioning
confidence: 99%
“…The initial model used in our laboratory is the Sprague-Dawley rat given injections of 25 μg estradiol benzoate on neonatal days 1, 3 and 5 of life ( Figure 1). It is important to mention that while this is considered "high-dose", the majority of neonatally administered estradiol is bound to α-fetoprotein which circulates at high levels in neonatal rat serum (42). Consequently, neonatal estradiol is 75-fold less potent than an equivalent dose of DES (43) or, put another way, 25 μg estradiol/pup is equivalent to 0.33 μg DES/pup.…”
Section: Rat Model Of Developmental Estrogenizationmentioning
confidence: 99%
“…Consideration should also be given to the fact that man-made chemicals, such as DES, which bind to estrogen receptors in cells, do not bind to estrogen-binding plasma proteins (93). One function of estrogen-binding plasma proteins, such as sexsteroid binding globulin in humans, is to restrict entry of endogenous estrogen into cells (94).…”
Section: Convincing Evidence Exists That a Variety Ofmentioning
confidence: 99%
“…This correlates with the estrogenic activities of E2 and DES estimated by the prepubertal mouse (Coldham et al 1997), although the extent of the difference was greater than the result in prepubertal mouse. The difference between the two systems may be due to the presence in vivo of binding proteins such as steroid hormone-binding globulin, which binds to DES more weakly than it binds to E2 (Sheehan & Young 1979), causing more DES to be available for ER binding. Secondly, the genes differed in their dose-dependent activation/repression patterns as we observed that the estrogens induced at least two different dose-response patterns.…”
Section: Dose-dependent Activation Of Genes By Physiological and Non-mentioning
confidence: 99%